(3EdbGe GdMLQ def SH CHj HcQ hYeQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; CeG HYO MeOG ddg abO SeYJ ef HYV GdeHJOFjf Cf SGH GdTjNjf CHj HcQ hYeQ QVj Gddg YfgeG JbHd TgGOJg agGdfj Pdc LOG ahVYJ gPg GdQSGdIs
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3dh cGf HYOj fHjG dcGf YeQ Hf GdNWGH (B" (3QhGg GdJQePj Yf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 158s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs